Pemanfaatan Potensi Kabupaten Sorong Selatan Melalui Pengolahan Ikan Sembilang Menjadi Bakso Ikan - Uun Lestari; Putri Meira Shyiang Sri; Anna Dara; Soraya Ramadani; Jasmani Jasmani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The community in Teminabuan generally only uses catfish (ikan sembilang) for daily consumption as a side dish. Therefore, there is a need for training activities on processing catfish into fish meatballs by utilizing the potential in Teminabuan District. Although several natural potentials exist in Teminabuan, this community service focuses on catfish as the training object. The main issue at the location is that, despite the abundant availability of catfish, processing it into value-added products is still very limited. The community has little knowledge about making fish meatballs from catfish or how to market the processed products. This activity aims to provide participants with knowledge and insights on how to produce fish meatball products from catfish, the benefits for family economics, how to design the products attractively for consumers, and how to market the products online. The methods used were lectures, mentoring, and hands-on practice. The results showed that participants understood how to process catfish into fish meatballs and gained knowledge on marketing the product. Throughout the activity, participants actively engaged in discussions and practical processing sessions. At the end, they had the opportunity to taste the catfish meatballs they created. Following this activity, it is expected that participants will be able to process catfish independently for family consumption, considering its high nutritional value, and foster an entrepreneurial spirit, especially among housewives and youth, to establish independent businesses that increase household income.